Answer:
x=3
Step-by-step explanation:
3(2x−4)−5(x−2)=1
Step 1: Simplify both sides of the equation.
3(2x−4)−5(x−2)=1
(3)(2x)+(3)(−4)+(−5)(x)+(−5)(−2)=1(Distribute)
6x+−12+−5x+10=1
(6x+−5x)+(−12+10)=1(Combine Like Terms)
x+−2=1
x−2=1
Step 2: Add 2 to both sides.
x−2+2=1+2
x=3
Answer: (2,-2)
Step-by-step explanation:
Rotating 90 degrees counterclockwise (about the origin) maps (x,y) onto (-y,x), so the answer is <u>N'(2,-2)</u>
the arrows on the end of the line means it continues
both the domain and the range for this graph is negative infinity to infinity
Answer:
33
Step-by-step explanation:
formula- radius X 2 = diameter x 3.14 | 22/7 = circumference
10 1/2 x 22/7 = 33